Voices Of Resistance: Nigerian Women and British Wartime Policies During the Second World War(1939-1945) - Disu, Oluyemisi Abayomi; Adesina, Oluwakemi Abiodun; Ekanade, Olumide Victor (Corpus Intellectual, 2024)
This study examines the role of women during the Second World War, highlighting their exclusion from decision-making as a significant economic development challenge. The involvement of women in the twentieth-century anti-colonial struggle, particularly their roles in social, financial, and political spheres, remains underexplored. Utilising archival sources, this research delves into women’s participation in the Second World War, their challenges, and their responses to wartime threats to their socioeconomic status and livelihoods. Employing historical methods and both primary and secondary sources, the study uncovers the involvement of women in colonial Nigeria during the war, with a focus on their opposition to British wartime policies. Despite their significant public roles prior to the war, British economic and political disenfranchisement altered women’s positions. The British imperial government’s new economic policies led to severe hardships for women, prompting demands for justice during the interwar years (1939 to 1945). The study concludes that the foodstuff price scheme was a turning point for Nigerian women, influencing the development of the underground economy (black market) in subsequent history.